A journal is a club: a new economic model for scholarly publishing - Potts, J.; Hartley, John; Montgomery, Lucy; Neylon, C.; Rennie, E. (2017)
A new economic model for the analysis of scholarly publishing – journal publishing in particular – is proposed that draws on club theory. The standard approach builds on market failure in the private production (by research scholars) of a public good (new scholarly knowledge). In this model, publishing is communication, as the dissemination of information. But a club model views publishing differently: namely as group formation, where members form groups in order to confer externalities on each other, subject to congestion. A journal is a self-constituted group, endeavouring to create new knowledge. In this sense, a journal is a club. The knowledge club model of a journal seeks to balance the positive externalities of a shared resource (readers, citations, referees) against the negative externalities of crowding (decreased prospect of publishing in that journal). A new economic model of a journal as a knowledge club is elaborated. We suggest some consequences for the management of journals and financial models that might be developed to support them.